ISSUE OF SCIENTIFIC-TECHNICAL DEVELOPMENT AND GERONTOLOGY (American Journal of Technology and Applied Sciences, 2024)
In the article, today's gerontology, that is, the science of aging, the ways of preventing old age and human aging, and the problems related to it, the development of science and technology, scientific discoveries, the use of various methods by people and its consequences, and the main causes of aging are analyzed based on a wide range of sources.